2022
DOI: 10.3390/atmos13091506
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Drought Variability in Northeast China over Multiple Temporal and Spatial Scales

Abstract: Long-term drought variation provides a scientific foundation for water resource planning and drought mitigation. However, the spatiotemporal variation characteristics of drought in northeast China (NEC) are unclear. We conducted a comprehensive assessment of drought status and trends based on the Standardized Precipitation Evapotranspiration Index (SPEI) in NEC from 1990 until 2018. The findings show that: (1) the drying trend peaked in 2001, and then exhibited a mitigation tendency before drying again after 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
2
1
0
Order By: Relevance
“…The SPEI has a flexible time scale and fully considers the influence generated by temperature, and the drought events obtained from the treatment tend to be consistent with previous research results [41,48]. Temporal changes in annual-scale drought in Northeast China had prominent interannual characteristics, with the most significant positive and…”
Section: Discussionsupporting
confidence: 85%
“…The SPEI has a flexible time scale and fully considers the influence generated by temperature, and the drought events obtained from the treatment tend to be consistent with previous research results [41,48]. Temporal changes in annual-scale drought in Northeast China had prominent interannual characteristics, with the most significant positive and…”
Section: Discussionsupporting
confidence: 85%
“…Figure 5a shows that the regions with the highest frequency of drought occurrence were mostly concentrated in west-central Jilin and southern Liaoning. SPEI monitored droughts of long duration and high severity mainly in northwestern Liaoning, southwestern Heilongjiang, and west-central Jilin, which was generally consistent with records, and the identification results were in general agreement with the findings of Xue et al [38].…”
Section: Spei Drought Event Identification In Typical Regionssupporting
confidence: 88%
“…Xue et al [25], conducted a comprehensive assessment of drought status and trends based on the Standardized Precipitation Evapotranspiration Index (SPEI) in Northeast China (NEC) from the period of 1990 until 2018. The authors found that NEC has exhibited a general dry tendency over the past three decades.…”
mentioning
confidence: 99%